Prediktor Mortalitas Pasien Sindrom Koroner Akut di Rumah Sakit X Jakarta Periode September 2023-2024 - Rante Tiku, Ristha Monica; Arsita, Elli; Oktavia, Eva (Jurnal MedScientiae, 2025)
Acute coronary syndrome (ACS) is the leading cause of death from heart disease worldwide. Several studies have identified risk factors that increase mortality among ACS patients, including advanced age, type 2 diabetes mellitus, and chronic kidney disease. This study aims to evaluate the association between these risk factors and mortality in ACS patients at Hospital X Jakarta between September 2023 and September 2024. Contains This study used a retrospective cohort design with analysis of medical record data of patients with ACS. Statistical analysis was performed using chi-squared and Fisher's exact tests to determine the association of age, type 2 diabetes mellitus, and chronic kidney disease with mortality in patients with ACS. Contains A total of 84 patients with a mean age of 59.49 years met the study criteria. The majority of patients had NSTEMI (61.9%) and 56% had type 2 diabetes mellitus. Mortality occurred in 4.8% of the patients. The results of the analysis showed that advanced age (≥60 years) was significantly associated with mortality in SCA patients (p=0.047; RR=4.50). Chronic kidney disease was also significantly associated with mortality (p=0.011; RR=8.16). However, type 2 diabetes mellitus did not show a significant association with mortality (p=0.092). Advanced age and chronic kidney disease were significant predictors of mortality in patients with ACS, whereas type 2 diabetes mellitus was not significantly associated with mortality.